(untitled) (International Journal of Food and Nutritional Sciences, 2021)
ACNP prepared by Mangifera Indica; Celostia Argentea doped with ZnO nanoparticles at various weight ratios 5; 10; 15; 20; and 25 wt%. They theoretically analyzed the function used with Gibbs free energy equation. Due to the novel materials and balls performance the still achieve the output of distillate 14.92 l/m2 day and efficiency upto 38.73%. U shape is also a novel work in the design of the solar still with construct with vapor tight.